A survey of patients' experience of pain and other symptoms while receiving care from palliative care services. Issue 3 (5th March 2015) - Pidgeon, Tanya; Johnson, Claire E; Currow, David; Yates, Patsy; Banfield, Maree; Lester, Leanne; Allingham, Sam F; Bird, Sonia; Eagar, Kathy
Abstract : Context: In Australia, patients at the end of life with complex symptoms and needs are often referred to palliative care services (PCSs), but little is known about the symptoms of patients receiving palliative care in different settings. Objective: To explore patients' levels of pain and other symptoms while receiving care from PCSs. Method: PCSs registered through Australia's national Palliative Care Outcomes Collaboration (PCOC) were invited to participate in a survey between 2008 and 2011. Patients (or if unable, a proxy) were invited to complete the Palliative Care Outcome Scale. Results: Questionnaires were completed for 1800 patients. One-quarter of participants reported severe pain, 20% reported severe 'other symptoms', 20% reported severe patient anxiety, 45% reported severe family anxiety, 66% experienced depressed feelings and 19% reported severe problems with self-worth. Participants receiving care in major cities reported higher levels of depressed feelings than participants in inner regional areas. Participants receiving care in community and combined service settings reported higher levels of need for information, more concerns about wasted time, and lower levels of family anxiety and depressed feelings when compared to inpatients. Participants in community settings had lower levels of concern about practical matters than inpatients. Conclusions: Patients receiving care from Australian PCSs have physical and psychosocial concerns that are often complex and rated as 'severe'. Our findings highlight the importance of routine, comprehensive assessment of patients' concerns and the need for Specialist Palliative Care clinicians to be vigilant in addressing pain and other symptoms in a timely, systematic and holistic manner, whatever the care setting.